Development of software for automised cycling training programs - Weber, S.; Schuhwirth, A.; Huff, C. B.; Platen, P. (International Journal of Computer Science in Sport, 2002)
Even though bicycles are commonly used as transport vehicles, cycling has gained popularity as a leisure sport. The training habits of most athletes do not comprise a training system as known from sport sciences. Therefore a training system based on scientific knowledge might support the physical education of these athletes. To produce these training programs for leisure cyclists, computer software was developed.